Análise comparativa da viabilidade econômica da produção de aguardente utilizando caldo decana-de-açúcar e açúcar comercial como matérias-primas - Barros, Vítor Lucas de Oliveira (Universidade Federal de São Carlos, 2020)
Brandy can be produced from various raw materials, which directly influence the sensory characteristics of the product, the production process and economic analysis. Brandy can be defined as an alcoholic beverage of 38 to 58% by volume, obtained from the lowering of the alcoholic content of the simple alcoholic distillate or by the distillation of the fermented must. Various raw materials can be used in the production of brandy, such as sugar cane, cereals, brown sugar, sugar beet, cane molasses, sugars in general, etc. The objective of this work was to analyze and compare the economic viability of brandy production using sugar and/or sugarcane as raw materials. Two modes of production were evaluated and compared in relation to the traditional production of cane brandy (or cachaça). In the first, only sugar was used as raw material and fermentation was carried out by selected yeast UFLA CA 11. In the second, 10 tests were carried out to analyze the production of brandy from 20% v/v of cane juice diluted to 15 ºBrix (approximately 300 liters) and 250 kg of sugar diluted to 15 ºBrix (approximately 1300 liters) using free-range yeast as a production catalyst. The experiment was carried out in the city of Dores do Turvo-MG and the type of sugar used was crystal, acquired in the CEASA market, located in Belo Horizonte. Initially, production using sugar did not seem viable, as it includes costs of planting sugar cane, costs of producing sugar and brandy, while direct fermentation of the sugarcane juice subtracts costs of sugar production (evaporation, crystallization, drying, etc.). However, profitability and low payback time were observed in the production of brandy with 20% cane juice. The fermentation process involving only sugar and selected yeast UFLA CA 11 has not been completed due to nutritional limitations that prevented the yeast from completely consuming the sugars present in the process.
Comparative analysis of the economic viability of brandy production using sugarcane juice and commercial sugar as raw materials
Keywords: Aguardente; Cachaça; Cana-de-açúcar; Análise de viabilidade econômica; Brandy; Sugarcane; Economic feasibility analysis; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA